EKSPERIMEN GAYA GESEK UNTUK MENGUJI NILAI KOEFISIEN GESEKAN STATIS KAYU PADA KAYU DENGAN PROGRAM MATLAB - Puji Hariati Winingsih; Hidayati Hidayati (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims at designing tools to test the coefficient of static timber friction on wood through friction force experiments. Crafting force experiments have been developed to determine the coefficient of static timber friction coefficient on wood. The data was collected 10 times each mass variation and obtained friction force data (fs). The data analysis used a weighted linear regression with REGLIN program written in Matlab and chisquere test. The results obtained by the form of coefficients of linear function are a0 = 0.309 and a1 = 1.937 with ralat (SÎ¼ = 0.010). The amount of coefficient of static friction (Î¼s) of wood on wood using Matlab is Î¼s = (0.402 Â± 0.010). This result is in accordance with the theory that Î¼s = 0.40. The chisqure test (Ï‡2) shows that there is a linear correlation between fs and m, with an opportunity value P () = 50.56%, so the data in this experiment is acceptable.Â